Evaluating TOEFL ITP Test: A Critical Review - Ahmad Amin Dalimunte; Ade Tika; Muhammad Dalimunte; Ayumi Pratiwy Tanjung; Irma Suryani (Humanitatis : Journal of Language and Literature, 2023)
The critical objective of this present study is to conduct substantial evaluation of TOEFL as a language assessment tool. Using a qualitative method, the authors of the present study evaluated various specific issues based on a set of predetermined criteria such as practicality, test reliability, validity, authenticity, and washback impact. The analysis indicates that TEOFL ITP is both feasible and dependable. The TOEFL's dependability is based on these three components. However, unless the ITP test is altered from the previously used TOEFL, the TOEFL ITP is as reliable as the TOEFL PBT. In theory, its trustworthiness is uncertain, and more investigation is needed. It is debatable whether the TOEFL ITP test items can accurately represent this task when utilized for the placement test. TOEFL ITP is a reliable English test. Knowing the TOEFL significance encourages test takers to enhance their English skills as part of the exam. More students want to take lessons to enhance their grades.